A first look at megabenthic community responses to seasonal change using the new Holyrood Subsea Observatory in Conception Bay, NL - Rylan J. Command; Fabio C. De Leo; Cynthia H. McKenzie; Katleen Robert (Progress in Oceanography, 2023)

Temporal dynamics of the deep-sea pink urchin Strongylocentrotus fragilis on the Northeast Pacific continental margin - Rylan J. Command; Fabio C. De Leo; Katleen Robert (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Benthic megafaunal biodiversity of the Charlie-Gibbs fracture zone: spatial variation, potential drivers, and conservation status - Poppy Keogh; Rylan J. Command; Evan Edinger; Aggeliki Georgiopoulou; Katleen Robert (Marine Biodiversity, 2022)
The Charlie-Gibbs Fracture Zone (CGFZ) is a prominent geological feature offsetting the Mid-Atlantic Ridge (MAR), consisting of two parallel fractures, creating a highly variable seafloor bathymetry. It has been defined as the most important latitudinal biodiversity transitional zone on the MAR. Despite this recognition, the faunal communities living on the fracture zone have not been extensively described. A remotely operated vehicle (ROV) was utilised during the TOSCA (Tectonic Ocean Spreading at the Charlie-Gibbs Fracture Zone) survey. The survey included five ROV video transects at depths between 560 and 2900 m. The objectives of the study were to use this video footage to quantify benthic megafaunal density and biodiversity patterns on the CGFZ and their environmental drivers. Species accumulation curves and generalised additive modelling show that depth and the presence of hard substrates play an important role in explaining species richness and abundance at the CGFZ. Coral taxa showed highest abundance between depths of 1500 and 2000 m, while sponge taxa were more abundant between 1750 and 2250 m. A dense sponge aggregation was identified on a ridge feature at 2250 m depth. The high biodiversity and presence of dense sponge aggregations and coral gardens found in this study highlight the need for detailed surveys to help support decisions made by governing bodies on the protection status of the CGFZ.

Reproductive biology and ecology of Pacific hagfish ( Eptatretus stoutii ) and black hagfish ( Eptatretus deani ) - Aharon G. Fleury; Eva M. MacLennan; Rylan J. Command; Francis Juanes (Journal of Fish Biology, 2021)
The reproductive biology of Pacific hagfish Eptatretus stoutii (Lockington, 1878) and black hagfish Eptatretus deani (Evermann & Goldsborough, 1907) was assessed using current and historical data. Our results found that the reproductive characteristics of both hagfish species reflect those of K ‐selected species, which tend to live long and exhibit slow growth rates, low fecundity (approximately 20 eggs per female) and late maturity. Additionally, females of both species commence maturation prior to males. This study provides a population profile for both species of hagfish, but further assessments are needed to effectively manage a sustainable hagfish fishery.